1999
DOI: 10.1128/jcm.37.5.1548-1553.1999
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Enzootic Babesiosis in Baboons (Papio cynocephalus) and Phylogenetic Evidence Supporting Synonymy of the GeneraEntopolypoidesandBabesia

Abstract: Blood smear evaluation of two baboons (Papio cynocephalus) experiencing acute hemolytic crises following experimental stem cell transplantation revealed numerous intraerythrocytic organisms typical of the genus Babesia. Both animals had received whole-blood transfusions from two baboon donors, one of which was subsequently found to display rare trophozoites of Entopolypoides macaci. An investigation was then undertaken to determine the prevalence of hematozoa in baboons held in our primate colony and to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Previously, a partial SSUrRNA sequence (PB-1; Figure 2A) was published of a new B. microti-like species that infected baboons. 2 The B. microti-like parasite SSUrRNA sequence from Ri12142 described here is clearly distinct from PB-1 (Figure 2A), revealing a new B. microti-like parasite that is capable of infecting a nonhuman primate.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Previously, a partial SSUrRNA sequence (PB-1; Figure 2A) was published of a new B. microti-like species that infected baboons. 2 The B. microti-like parasite SSUrRNA sequence from Ri12142 described here is clearly distinct from PB-1 (Figure 2A), revealing a new B. microti-like parasite that is capable of infecting a nonhuman primate.…”
mentioning
confidence: 81%
“…1 Babesia-like parasites of the genus Entopolypoides macaci have been reported to infect nonhuman primates; based on phylogenetic analysis of small-subunit rRNA (SSUrRNA) sequences of this parasite and on serological and epidemiological data, it was suggested that the genus Entopolypoides is synonymous with that of Babesia. 2 In primate centers, natural infections with this parasite have been shown in baboons (Papio cynocephalus), 2 long-tailed macaques (Macaca fascicularis), 3 and rhesus macaques (Macaca mulatta), 4 providing animal models in species closely related to humans to study parasite-host relationships of this pathogen.…”
mentioning
confidence: 99%
“…As a result of this infection, which occurred at the Regional Primate Center in Washington State in the USA, an investigation was undertaken to determine the prevalence of hematozoa in baboons at that primate colony [16]. The incidence was 39% in colony-bred baboons, 35% in baboons that had been transferred from out-of-state breeding facilities, and 12% in baboons imported from Africa.…”
Section: Discussionmentioning
confidence: 99%
“…This result does not necessarily indicate that B. rodhaini is actually infectious and pathogenic to humans. However, precautions should be taken against this and other B. microti-like parasites that have increasingly been reported from a wide variety of wild animals [2,5,8,9,21,38] as a group of potentially zoonotic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, both B. rodhaini and B. microti have wide host ranges, and susceptible laboratory animals include mice, rats, hamsters, gerbils, and monkeys [10,23,25,27]. Natural infections by parasites closely related to B. microti or B. rodhaini have increasingly been reported in dogs [38], cats [8], lions [21], foxes [9], skunks [9], raccoons [2], and baboons [5]. Nonetheless, B. microti sensu stricto ("clade 1" in the reference [9]) is currently regarded as the sole etiologic agent of human babesiosis within the group of parasites.…”
mentioning
confidence: 99%